Incidence and Result of Treatment-Demanding Retinopathy of Prematurity Using Revised U.S. Screening Guidelines - Kuo, Hsi-Kung; Chen, Chih-Cheng; Chen, Yi-Hao; Huang, Hsin-Chun; Liu, Chieh-An; Chen, Feng-Shun; Chung, Mei-Yung (American Journal of Perinatology, 2012)
Objective To study the incidence of treated retinopathy of prematurity (ROP) using the revised U.S. screening guidelines, the rate of missed treatment, and unfavorable anatomic outcomes over a period of 2 years.Study Design We reviewed the admission records of premature patients treated at our hospital from September 2008 to August 2010. Any baby born with a gestational age (GA) of less than 30 weeks or a birth body weight (BW) of less than 2000 g was included in this study. The ROP screening followed the revised U.S. screening guidelines as presented in 2006. The indications of treatment for ROP were threshold disease as defined by the Multicenter Trial of Cryotherapy for Retinopathy of Prematurity study and type 1 prethreshold ROP as defined by the Early Treatment for Retinopathy of Prematurity Randomized Trial study.Results There were 385 infants who were examined for ROP screening during this period. Nineteen babies (35 eyes) fit the treatment criteria and received treatment. The incidence of treatment-demand ROP was 4.9% (19/385). Four babies had a birth BW >1500 g (4/19; 21%). Seventeen babies received treatment during their first admission and two babies received treatment during outpatient follow-up. No baby missed timely treatment. Three eyes progressed to stage 4/5 after receiving intravitreal bevacizumab treatment. The success rate after primary bevacizumab was 91% (30/33 eyes).Conclusion The incidence of treatment-demanding ROP using revised U.S. screening criteria was 4.9%. Teamwork and cooperation are very important to ensure that the highest-quality care possible is provided to patients in a timely manner.
Keywords: retinopathy of prematurity; screening programs and criteria; gestational age; birth body weight